A denitration catalyst and its preparation method and application

By using a denitrification catalyst composed of indium, H-Beta molecular sieve and nickel-manganese composite oxide, the problems of high reaction temperature and low CH4 conversion in the prior art are solved, and low temperature and efficient NOx removal and CH4 conversion are achieved, and energy savings are achieved.

CN116174027BActive Publication Date: 2025-03-21HARBIN INST OF TECH SHENZHEN GRADUATE SCHOOL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310227803.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-28
Publication Date
2025-03-21
Estimated Expiration
2043-02-28

AI Technical Summary

Technical Problem

The existing denitrification catalysts have problems such as high reaction temperature, low CH4 conversion rate and large energy consumption, making it difficult to achieve efficient NOx removal and CH4 conversion under low temperature conditions.

Method used

A denitrification catalyst composed of indium, H-Beta molecular sieve and nickel-manganese composite oxide is used to support the nickel-manganese composite oxide on the surface of the H-Beta molecular sieve through hydrothermal method and ion exchange method to form a nano-layer structure.

Benefits of technology

It realizes the denitrification effect of rapid activation under low temperature conditions, high CH4 conversion rate and high NOx removal rate, and saves energy consumption of denitrification equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004119131770000111
    Figure BDA0004119131770000111
  • Figure BDA0004119131770000112
    Figure BDA0004119131770000112
  • Figure BDA0004119131770000121
    Figure BDA0004119131770000121
Patent Text Reader

Abstract

The present invention discloses a denitration catalyst and its preparation method and application. The denitration catalyst of the present invention comprises indium, H-Beta molecular sieve and nickel-manganese composite oxide, wherein the indium and nickel-manganese composite oxide are both loaded on the surface of the H-Beta molecular sieve; the preparation method of the denitration catalyst comprises the following steps: 1) after mixing permanganate, H-Beta molecular sieve and nickel salt, adding divalent manganese salt, performing hydrothermal reaction and first roasting to obtain nickel-manganese modified H-Beta molecular sieve; 2) mixing the nickel-manganese modified H-Beta molecular sieve and indium salt, performing ion exchange and second roasting to obtain a denitration catalyst. The denitration catalyst of the present invention not only has fast activation, high CH4 conversion rate and NO x It has the advantages of high removal rate, simple preparation, controllable, low cost and energy saving, and is particularly suitable for application in CH4-SCR denitrification equipment or processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular to a denitration catalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of industry and transportation, nitrogen oxides (NO x ) Pollution is becoming more and more serious. x It is one of the main causes of a series of serious air pollution such as acid rain and photochemical smog, which affect human health and living environment. At present, CH4 is used as a reducing agent to selectively reduce NO x The denitration technology of (CH4-SCR) has attracted extensive attention from scholars at home and abroad, and the research on denitration catalysts has always been the key in this technology. In the existing technology, researchers generally use molecular sieves loaded with In-containing catalysts to improve the conversion rate of CH4, but this catalyst still has problems such as high reaction temperature, low CH4 conversion rate, and high energy consumption.

[0003] Therefore, it is urgent to develop a denitration catalyst with low reaction temperature and good comprehensive CH4-SCR denitration performance. Summary of the invention

[0004] In order to overcome the technical problems of high reaction temperature and high energy consumption of denitration catalysts in the prior art, the object of the present invention is to provide a low-temperature CH4-SCR denitration catalyst and a preparation method and application thereof.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect, the present invention provides a denitration catalyst comprising indium, H-Beta molecular sieve and nickel-manganese composite oxide, wherein the indium and nickel-manganese composite oxide are both loaded on the surface of the H-Beta molecular sieve.

[0007] Preferably, the nickel-manganese composite oxide includes one or more of MnO2 and NiMnO3.

[0008] Further preferably, the nickel-manganese composite oxide includes one or more of α-crystalline MnO2, δ-crystalline MnO2, and NiMnO3.

[0009] Preferably, the nickel-manganese composite oxide is in nano-layered form.

[0010] Specifically, the nickel-manganese composite oxide is nano-layered, which specifically means that the nickel-manganese composite oxide is a nano material and can present a nano-sheet structure.

[0011] Preferably, the ratio of the molar amount of the nickel-manganese composite oxide to the mass of the H-Beta molecular sieve is 0.05 mmol / g to 2 mmol / g.

[0012] Preferably, the molar ratio of nickel to manganese in the nickel-manganese composite oxide is 1:0.5 to 1:5.

[0013] More preferably, the molar ratio of nickel to manganese in the nickel-manganese composite oxide is 1:1 to 1:2.5.

[0014] Preferably, the particle size of the H-Beta molecular sieve is 50 nm to 400 nm.

[0015] More preferably, the mass ratio of the molar amount of the nickel-manganese composite oxide to the H-Beta molecular sieve is 0.1 mmol / g to 2 mmol / g.

[0016] Preferably, the specific surface area of ​​the denitration catalyst is 300m 2 / g~330m 2 / g.

[0017] Preferably, the average pore size of the denitration catalyst is 4 nm to 8 nm.

[0018] In a second aspect, the present invention provides a method for preparing the denitration catalyst according to the first aspect, comprising the following steps:

[0019] 1) After mixing permanganate, H-Beta molecular sieve and nickel salt, divalent manganese salt is added, and the mixture is subjected to hydrothermal reaction and first calcination to obtain nickel-manganese modified H-Beta molecular sieve;

[0020] 2) The nickel-manganese modified H-Beta molecular sieve of step 1) is mixed with indium salt, and subjected to ion exchange and a second calcination to obtain a denitration catalyst.

[0021] Preferably, the ratio of the molar amount of manganese in step 1) to the molar amount of nickel in the nickel salt is 1:0.5 to 1:5.

[0022] Further preferably, the ratio of the molar amount of manganese in step 1) to the molar amount of nickel in the nickel salt is 1:1 to 1:2.5.

[0023] Specifically, the total amount of manganese in step 1) refers to the sum of the molar amount of manganese in the permanganate and the molar amount of manganese in the divalent manganese salt.

[0024] Preferably, in step 1), the molar ratio of the permanganate to the divalent manganese salt is 2:1 to 10:1.

[0025] Further preferably, in step 1), the molar ratio of the permanganate to the divalent manganese salt is 4:1 to 8:1.

[0026] Preferably, the ratio of the molar amount of manganese in step 1) to the mass of the H-Beta molecular sieve is 0.1 mmol / g to 5 mmol / g.

[0027] More preferably, the ratio of the molar amount of manganese in step 1) to the mass of the H-Beta molecular sieve is 0.5 mmol / g to 1.5 mmol / g.

[0028] More preferably, the ratio of the molar amount of manganese in step 1) to the mass of the H-Beta molecular sieve is 0.8 mmol / g to 1.2 mmol / g.

[0029] Preferably, the temperature of the hydrothermal reaction in step 1) is 120°C to 200°C.

[0030] Further preferably, the temperature of the hydrothermal reaction in step 1) is 150°C to 180°C.

[0031] Preferably, the hydrothermal reaction time in step 1) is 6 h to 20 h.

[0032] Further preferably, the hydrothermal reaction time in step 1) is 10 h to 16 h.

[0033] Preferably, the first calcination in step 1) is carried out under a protective gas atmosphere.

[0034] Preferably, the temperature of the first calcination in step 1) is 250°C to 550°C.

[0035] Further preferably, the temperature of the first calcination in step 1) is 300°C to 500°C.

[0036] Preferably, the inert atmosphere is one or more of nitrogen, argon and helium.

[0037] Preferably, the first calcination time in step 1) is 1 h to 10 h.

[0038] Preferably, the first calcination time in step 1) is 2 h to 5 h.

[0039] Preferably, the permanganate in step 1) is one or more of potassium permanganate and sodium permanganate.

[0040] Preferably, the nickel salt in step 1) is one or more of nickel nitrate, nickel sulfate, nickel chloride, nickel nitrate hydrate, nickel sulfate hydrate, and nickel chloride hydrate.

[0041] Preferably, the divalent manganese salt in step 1) is one or more of manganese sulfate, manganese chloride, manganese nitrate, a hydrate of manganese sulfate, a hydrate of manganese chloride, and a hydrate of manganese nitrate.

[0042] Preferably, the indium salt in step 2) is one or more of indium nitrate and indium nitrate hydrate.

[0043] Further preferably, in step 2), the indium salt is an aqueous solution containing indium nitrate, and the concentration of the aqueous solution containing indium nitrate is 0.01 mol / L to 0.1 mol / L.

[0044] More preferably, the ratio of the mass of the H-Beta molecular sieve in step 1) to the volume of the indium salt in step 2) is 5 to 15 mg / mL.

[0045] Preferably, the temperature of the ion exchange in step 2) is 70°C to 95°C.

[0046] Preferably, the ion exchange time in step 2) is 5 h to 15 h.

[0047] Preferably, the second calcination in step 2) is carried out in an air atmosphere.

[0048] Preferably, the temperature of the second calcination in step 2) is 250°C to 550°C.

[0049] Further preferably, the temperature of the second calcination in step 2) is 300° C. to 500° C. Preferably, the time of the second calcination in step 2) is 2 h to 6 h. Preferably, step 1) and step 2) further include the steps of stirring, centrifuging, washing the precipitate, and drying.

[0050] In a third aspect, the present invention provides a denitration device, comprising the denitration catalyst.

[0051] In a fourth aspect, the present invention provides use of the above-mentioned denitration catalyst in a selective catalytic reduction reaction.

[0052] Preferably, the reaction gas in the selective catalytic reduction reaction includes NO x and CH4.

[0053] Further preferably, the reaction gas in the selective catalytic reduction reaction includes 100 ppm to 1000 ppm of NO x And 100ppm~1000ppm CH4.

[0054] Preferably, the temperature of the selective catalytic reduction reaction is 150°C to 650°C.

[0055] Preferably, sulfur dioxide is not included in the selective catalytic reduction reaction.

[0056] Preferably, the space velocity of the reaction gas in the selective catalytic reduction reaction is 10000h -1 ~40000h -1.

[0057] The beneficial effects of the present invention are: the denitration catalyst of the present invention not only has fast activation under low temperature conditions, high CH4 conversion rate, and NO x The advantage of high removal rate is that it can also save energy for denitrification equipment. Specifically:

[0058] (1) The denitration catalyst of the present invention comprises indium, H-Beta molecular sieve and nickel-manganese composite oxide, wherein the indium is loaded on the H-Beta molecular sieve by an ion exchange method, and the nano-layered nickel-manganese composite oxide is loaded on the surface of the H-Beta molecular sieve by a hydrothermal method;

[0059] (2) The nickel-manganese composite oxide of the present invention is in the form of thin flakes and is uniformly loaded on the surface of the In-modified H-Beta molecular sieve, and the loading of the nickel-manganese composite oxide and In does not change the framework structure of the H-Beta molecular sieve;

[0060] (3) The preparation method of the denitration catalyst of the present invention is not only simple, controllable, convenient and low-cost, but also the prepared catalyst can form a good chemical synergy between the nickel-manganese composite oxide and In / H-Beta, increase the strength and number of the acid sites of the catalyst, improve the redox property of the catalyst, and increase the InO + The number of active sites promotes the activation of CH4 and NO x 's transformation;

[0061] (4) Compared with the In / H-Beta catalyst, the NiMn2@In / H-Beta type catalyst can improve the low-temperature denitration catalytic activity of CH4-SCR with a small amount of nickel-manganese composite oxide through synergistic effect, and can also achieve a high CH4 conversion rate at 450-550°C;

[0062] (5) NiMn2@In / H-Beta-1-400 in the present invention has NO at 250°C x The conversion rate begins to change; at 400℃, NO x The conversion rate is close to 50%, which is higher than that of In / H-Beta catalyst NO at the same temperature. x The conversion rate is more than twice; at 450℃, NO x The conversion rate reached about 95%, which was nearly 100°C lower than that of the In / H-Beta catalyst, showing good low-temperature activity and high CH4 selectivity.

[0063] (6) The denitration catalyst of the present invention can be applied to denitration technology to achieve NO below 450°C. xThe conversion rate reaches 95%, thereby achieving the technical effect of saving the energy consumption of the denitration equipment by the denitration catalyst, and is therefore suitable for application in the CH4-SCR denitration technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 MnO2, CoMn2O in Comparative Example 1 x 、ZnMn2O x and NiMn2O x Figure 3 shows the results of the denitrification catalytic activity test.

[0065] Figure 2 XRD spectra of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2.

[0066] Figure 3 These are SEM images of the H-Beta molecular sieve, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2.

[0067] Figure 4 This is a graph showing the test results of the denitrification catalytic activity of the In / H-Beta catalyst in Comparative Example 3, the NiMn@In / H-Beta and NiMn2@In / H-Beta in Example 1.

[0068] Figure 5 It is the H2-TPR curve diagram of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2.

[0069] Figure 6 This is a graph showing the test results of the denitrification catalytic activity of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2.

[0070] Figure 7 Mn 2p is the Mn 2p of H-Beta molecular sieve, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2. 3 / 2 XPS spectrum.

[0071] Figure 8Ni 2p of NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2 3 / 2 XPS spectrum.

[0072] Fig. 9 It is the O1s XPS spectrum of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2.

[0073] Fig.10 The In 3d of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2 5 / 2 XPS spectrum.

[0074] Fig.11 NH3-TPD curves of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2.

[0075] Fig.12 NiMn2O in Comparative Example 2 x -300, NiMn2O x -400 and NiMn2O x -500's XRD spectrum.

[0076] Fig.13 This is a graph showing the test results of the denitrification catalytic activity of NiMn2@In / H-Beta-1-300NiMn2@In / H-Beta-1-400 and NiMn2@In / H-Beta-1-500 in Example 3.

[0077] Fig.14 This is the HRTEM image of NiMn2@In / H-Beta-1-400 in Example 3.

[0078] Fig.15 FTIR spectra of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2. DETAILED DESCRIPTION

[0079] The present invention is further described in detail below through specific examples.

[0080] Unless otherwise specified, the reagents in the present invention are all commercially available; the molar amount of manganese (Mn) in the "nickel-manganese ratio", "Ni / Mn" and "Ni:Mn" in the present embodiments and comparative examples is the sum of the molar amounts of KMnO4 and MnSO4; the H-Beta molecular sieves used in the present invention are all nanometer-level; the loading amount y (in mmol) in the present embodiment is the theoretical loading amount, which means the ratio of the total molar amount of Mn to the mass of the H-Beta molecular sieve; the catalysts or materials provided in the embodiments and comparative examples of the present invention all adopt the same catalyst evaluation method.

[0081] Example 1

[0082] This embodiment provides a denitration catalyst with different nickel-manganese ratios. The denitration catalyst with different nickel-manganese ratios is specifically a nickel-manganese composite oxide modified In / H-Beta catalyst with different nickel-manganese ratios, denoted as NiMn x @In / H-Beta (loading amount y is 0.5 mmol Mn / g H-Beta molecular sieve, x=1, 2); when the molar ratio of Ni and Mn in the precursor liquid is 1:1, the nickel-manganese composite oxide modified In / H-Beta catalyst is recorded as NiMn@In / H-Beta; when the molar ratio of Ni and Mn in the precursor liquid is 1:2, the nickel-manganese composite oxide modified In / H-Beta catalyst is recorded as NiMn2@In / H-Beta.

[0083] This embodiment also provides a method for preparing the above nickel-manganese composite oxide modified In / H-Beta catalyst, comprising the following steps:

[0084] 1) Weigh 2 portions of 1.5 g H-Beta molecular sieve respectively, and calculate and weigh 2 portions of KMnO4 and MnSO4 according to the dosage ratio of different reagents and the specific loading amount y; dissolve KMnO4 in 80 mL of deionized water, and stir evenly to obtain 2 portions of KMnO4 solution;

[0085] According to Ni:Mn=1:1, 1:2 (molar ratio), calculate and weigh 2 parts of Ni(NO3)2·6H2O with different masses, add 1 part of KMnO4 solution to each, and after complete dissolution, add 1 part of MnSO4 and H-Beta molecular sieve respectively, stir well with a magnetic stirrer, and react for 1 hour to obtain 2 parts of precursor liquid;

[0086] 2) The two precursor solutions in step 1) were transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor lining, and then subjected to a hydrothermal reaction at a reaction temperature of 160°C and a reaction time of 12 h. The mixture was naturally cooled to room temperature, and the brown precipitate was collected by centrifugation and washed with deionized water several times. After drying at 80°C in a forced air drying oven overnight, the mixture was calcined at 500°C for 3 h in a N2 atmosphere to obtain two nickel-manganese-modified H-Beta molecular sieves (denoted as NiMn x @H-Beta);

[0087] 3) Add the two nickel-manganese modified H-Beta molecular sieves in step 2) and 0.033M In(NO3)3 solution (i.e., ion exchange solution, the solvent is water) into a beaker in proportion, and then place the beaker in an 85°C oil bath and stir for 8 hours. After ion exchange, filter, wash, precipitate, dry and grind to obtain two powders;

[0088] The two powders were placed in a tube furnace for calcination, and the calcination atmosphere was set to air, the calcination temperature was set to 500°C, and the calcination time was set to 3 hours, and finally two nickel-manganese composite oxide modified In / H-Beta catalysts (i.e., NiMn@In / H-Beta and NiMn2@In / H-Beta) were obtained;

[0089] Wherein, in the two precursor solutions of step 1), the molar ratio of KMnO4 to MnSO4 is 95:16;

[0090] In the precursor solution of step 1), the ratio of the molar amount of Mn to the mass of the H-Beta molecular sieve is 0.5 mmol / g;

[0091] In step 3), the usage ratio of H-Beta molecular sieve and 0.033M In(NO3)3 solution is 500 mg / 50 mL.

[0092] Example 2

[0093] The present embodiment provides denitration catalysts with different nickel-manganese composite oxide loadings. The denitration catalysts with different nickel-manganese composite oxide loadings are specifically nickel-manganese composite oxide modified In / H-Beta catalysts, recorded as NiMn2@In / H-Beta-y (y represents the loading amount, the value range of y is: y=0.5, 1 or 1.5, and the unit of y is: mmol / g).

[0094] This embodiment also provides a method for preparing the above nickel-manganese composite oxide modified In / H-Beta catalyst, comprising the following steps:

[0095] 1) Weigh 3 portions of 1.5 g H-Beta molecular sieve respectively, and weigh 3 groups of KMnO4 and MnSO4 according to the dosage ratio of specific reagents and the calculation of different loading amounts y; dissolve KMnO4 in 80 mL of deionized water, and stir evenly to obtain 3 groups of KMnO4 solutions;

[0096] Weigh 3 parts of Ni(NO3)2·6H2O according to Ni:Mn=1:2 (molar ratio), add KMnO4 solution, add MnSO4 of each group after it is completely dissolved, and then add 1 part of H-Beta molecular sieve to each group, stir well with a magnetic stirrer, and react for 1 hour to obtain 3 precursors;

[0097] 2) The three precursor liquids in step 1) were transferred to a 100 mL polytetrafluoroethylene hydrothermal autoclave liner, and then subjected to a hydrothermal reaction at a reaction temperature of 160° C. and a reaction time of 12 h. The mixture was naturally cooled to room temperature, and the brown precipitate was collected by centrifugation. The precipitate was washed with deionized water several times, dried at 80° C. in a forced air drying oven overnight, and then calcined at 500° C. for 3 h in a N2 atmosphere to obtain three nickel-manganese-modified H-Beta molecular sieves (denoted as NiMn2@H-Beta).

[0098] 3) Add the three nickel-manganese modified H-Beta molecular sieves and 0.033M In(NO3)3 solution (i.e., ion exchange solution, the solvent is water) in step 2) into a beaker in proportion, and then place the beaker in an 85°C oil bath while stirring for 8 hours to perform ion exchange, and obtain a powder by suction filtration, washing, precipitation, drying, and grinding;

[0099] The powder was placed in a tube furnace for calcination, and the calcination atmosphere was set to air, the calcination temperature was set to 500°C, and the calcination time was set to 3 hours, and finally a nickel-manganese composite oxide modified In / H-Beta catalyst (i.e., NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1.0 and NiMn2@In / H-Beta-1.5) was obtained;

[0100] Among them, the molar ratio of KMnO4 and MnSO4 in the three precursor solutions of step 1) is 95:16; the loading amount y of step 1) is 0.5 mmol / g, 1.0 mmol / g, and 1.5 mmol / g respectively; the calculation formula of the loading amount y of step 1) is as follows:

[0101] y=(n(KMnO4)+n(MnSO4)) / m(H-Beta molecular sieve),

[0102] In the formula, n(KMnO4) represents the amount of KMnO4, n(MnSO4) represents the amount of MnSO4, and m(H-Beta molecular sieve) represents the mass of H-Beta molecular sieve;

[0103] Step 3) also requires controlling the usage ratio of H-Beta molecular sieve and 0.033M In(NO3)3 solution to 500 mg / 50 mL.

[0104] Example 3

[0105] This embodiment provides a denitration catalyst with different calcination temperatures. The denitration catalyst is specifically a nickel-manganese composite oxide modified In / H-Beta catalyst, recorded as NiMn2@In / H-Beta-1-z (1 represents a loading amount of 1 mmol / g, z represents a calcination temperature, and the value range of z is y=300, 400, 500).

[0106] This embodiment also provides a method for preparing the above nickel-manganese composite oxide modified In / H-Beta catalyst, comprising the following steps:

[0107] 1) Weigh 3 portions of 1.5 g H-Beta molecular sieve respectively, and calculate and weigh 3 portions of KMnO4 and MnSO4 according to the dosage ratio of the specific reagent and the loading amount y; dissolve KMnO4 in 80 mL of deionized water, and stir evenly to obtain 3 portions of KMnO4 solution;

[0108] According to Ni:Mn=1:2 (molar ratio), calculate and weigh 3 parts of Ni(NO3)2·6H2O with different masses, add 1 part of KMnO4 solution to each, and after complete dissolution, add 1 part of MnSO4 and H-Beta molecular sieve, stir well with a magnetic stirrer, and react for 1 hour to obtain 3 parts of precursor liquid;

[0109] 2) The three precursor liquids in step 1) were transferred to the inner lining of a 100 mL polytetrafluoroethylene hydrothermal autoclave, and then subjected to a hydrothermal reaction at a reaction temperature of 160° C. and a reaction time of 12 h. The mixture was naturally cooled to room temperature, and the brown precipitate was collected by centrifugation and washed with deionized water for several times. The precipitate was dried overnight at 80° C. in a forced air drying oven to obtain three dried precipitates. The three dried precipitates were calcined at 300° C., 400° C., and 500° C. for 3 h under a N2 atmosphere to obtain three nickel-manganese-modified H-Beta molecular sieves (denoted as NiMn2@H-Beta-300, NiMn2@H-Beta-400, and NiMn2@H-Beta-500).

[0110] 3) Add the three nickel-manganese modified H-Beta molecular sieves in step 2) and 0.033M In(NO3)3 solution (i.e., ion exchange solution, the solvent is water) into a beaker in proportion, and then place the beaker in an 85°C oil bath while stirring for 8 hours to perform ion exchange, and obtain a powder by suction filtration, washing precipitation, drying, and grinding;

[0111] The powder was placed in a tube furnace for calcination under air atmosphere at 300°C, 400°C and 500°C for 3 h, respectively, to obtain three kinds of nickel-manganese composite oxide modified In / H-Beta catalysts.

[0112] Wherein, the molar amount of Mn in the precursor solution of step 1) and the mass ratio of H-Beta molecular sieve are 1.0 mmol / g (i.e., the loading amount y is 1.0 mmol / g); the amount ratio of H-Beta molecular sieve and 0.033M In(NO3)3 solution in step 3) is 500 mg / 50 mL;

[0113] When the calcination temperature of step 2) and step 3) is both 300°C, a nickel-manganese composite oxide modified In / H-Beta catalyst (NiMn2@In / H-Beta-1-300) is finally obtained; when the calcination temperature of step 2) and step 3) is both 400°C, a nickel-manganese composite oxide modified In / H-Beta catalyst (NiMn2@In / H-Beta-1-400) is finally obtained; when the calcination temperature of step 2) and step 3) is both 500°C, a nickel-manganese composite oxide modified In / H-Beta catalyst (NiMn2@In / H-Beta-1-500) is finally obtained.

[0114] Comparative Example 1

[0115] This comparative example provides a denitration catalyst doped with different metals. The denitration catalyst doped with different metals is specifically a manganese-based composite oxide doped with different metals, which are respectively denoted as MnO2, CoMn2O x 、ZnMn2O x 、NiMn2O x .

[0116] (1) Preparation method of MnO2

[0117] Refer to the preparation method of MnO2 in “Insights into the surface-defect dependence of molecular oxygen activation over birnessite-type MnO2(https: / / doi.org / 10.1016 / j.apcatb.2018.03.107)” published by Yang et al. in the journal Applied Catalysis B: Environmental in 2018.

[0118] This comparative example provides a method for preparing MnO2, comprising the following steps:

[0119] After dissolving 1.0 g KMnO4 and 0.15 g MnSO4·H2O in 70 mL deionized water, the mixture was transferred to a hydrothermal reactor and reacted at 200°C for 12 hours. After the hydrothermal reactor was cooled to room temperature, the precipitate was centrifuged and washed, dried at 105°C for 24 hours, and then calcined at 300°C for 3 hours to obtain MnO2.

[0120] (2) Preparation methods of manganese oxides doped with other different metals

[0121] This comparative example also provides a method for preparing the above-mentioned manganese oxide doped with different metals, comprising the following steps:

[0122] 1) Co(NO3)2·6H2O, Zn(NO3)2·6H2O, and Ni(NO3)2·6H2O were used as metal doping sources respectively; three metal doping sources, MnO2 in this comparative example, and 80 mL of water were weighed in proportion, added into three groups of hydrothermal reaction kettles, and hydrothermal reaction was carried out at a temperature of 160°C and a reaction time of 12 h. After centrifugation, washing, precipitation, and drying, a precipitate was obtained;

[0123] 2) The precipitate was calcined at 500°C for 3 h to obtain manganese oxides doped with different metals, which can be recorded as CoMn2O x 、ZnMn2O x 、NiMn2O x ;

[0124] Wherein, the molar ratio of the metal in the metal doping source in step 1) to the Mn in MnO2 is 1:2.

[0125] Comparative Example 2

[0126] This comparative example provides a method for preparing nickel-manganese composite oxides at different calcination temperatures. The main difference between this comparative example and Example 1 is that this comparative example does not include the steps of "step 1) adding H-Beta molecular sieve and step 3) using an ion exchange reagent (0.033MIn(NO3)3 solution) to modify the H-Beta molecular sieve", and specifically includes the following steps:

[0127] 1) Weigh 1.5 g of KMnO4 (9.5 mmol) and dissolve it in 80 mL of deionized water. Stir evenly to obtain a KMnO4 solution.

[0128] According to the molar ratio of Ni:Mn=1:2, Ni(NO3)2·6H2O was weighed, and KMnO4 solution was added. After it was completely dissolved, 0.275g MnSO4 (1.6mmol) was added, and the mixture was fully stirred with a magnetic stirrer. After reacting for 1h, a nickel-manganese precursor solution was obtained;

[0129] 2) The nickel-manganese precursor solution in step 1) was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor lining, and the reaction was carried out at 160° C. for 12 h. The mixture was naturally cooled to room temperature, and the brown precipitate was collected by centrifugation and washed with deionized water several times. After drying at 80° C. in a blast drying oven overnight, the mixture was calcined at 300° C., 400° C., and 500° C. for 3 h in a N2 atmosphere to obtain three nickel-manganese composite oxides (denoted as NiMn2O x -300, NiMn2O x -400 and NiMn2O x -500).

[0130] Comparative Example 3

[0131] This comparative example provides a method for preparing an In / H-Beta catalyst, comprising the following steps:

[0132] 1) Add 1.5 g H-Beta molecular sieve and 0.033 M In(NO3)3 solution (i.e. ion exchange solution, the solvent is water) into a beaker, and then place the beaker in an 85°C oil bath while stirring for 8 hours to perform ion exchange, and then filter, wash, precipitate, dry, and grind to obtain a powder;

[0133] 2) The powder was placed in a tube furnace for calcination, and the calcination atmosphere was set to air, the calcination temperature was set to 500° C., and the calcination time was set to 3 h, and finally an In / H-Beta catalyst (abbreviated as: In / H-Beta) was obtained.

[0134] Application Examples

[0135] 1. Catalytic activity evaluation device

[0136] The evaluation device used in the activity evaluation experiment of the catalyst used in the present invention includes a gas path control system, a fixed bed reaction system and an online analysis and testing system.

[0137] In the gas control system, the gas circuits for activity evaluation include CH4 / Ar (5000ppm), NO / Ar (2000ppm), O2 (95vol%) and high-purity argon (balance gas), and all gases are provided by cylinder gas. The pressure of all gas circuits is controlled at 0.1MPa through a pressure-stabilizing valve, and the flow of each gas circuit is adjusted by a mass flow meter and merged into a mixing tube. After sufficient mixing, the gas enters the fixed reaction bed for programmed temperature reaction.

[0138] In the fixed bed reaction system, the fixed reaction bed is mainly composed of a reaction tube, a resistance furnace and a temperature controller. The reaction tube is a quartz glass tube with an inner diameter of 6 mm and an outer diameter of 10 mm. The catalyst is placed in the middle of the quartz tube through quartz wool support, and the resistance furnace is controlled by the temperature controller for programmed heating and insulation.

[0139] The online detection system consists of two parts: a gas chromatograph and a nitrogen oxide analyzer. The gas chromatograph is equipped with a methane converter, using nitrogen as the carrier gas, and the detector is a hydrogen flame ionization detector. The gas used for ignition is hydrogen, and the combustion-supporting gas is dry air. At the same time, hydrogen is also used as a protective gas for the nickel catalyst in the methane converter. When evaluating the activity of the catalyst, the reacted gas is first passed through a drying tube for drying to remove water vapor in the mixed gas, and then the dried gas is passed through a gas chromatograph and a nitrogen oxide analyzer to detect the conversion of methane and nitrogen oxides respectively.

[0140] 2. Catalytic activity evaluation method

[0141] This application example uses programmed surface temperature reaction (TPSR) to evaluate the activity of the catalyst and provides a method for evaluating a denitration catalyst, which specifically includes the following steps:

[0142] 1) 100 mg of catalyst was loaded into a quartz glass tube, and the total flow rate of the reaction gas was set to 100 mL / min and the reaction gas space velocity was set to 23600 h -1 , and the concentrations of the components of the reaction gas are controlled to be: 400 ppm NO, 400 ppm CH4, 10 vol.% O2, and high-purity argon is used as the balance gas;

[0143] 2) Before the programmed temperature rise, the catalyst is first pretreated at 100°C for 40 minutes under the reaction atmosphere to remove other gases adsorbed on the catalyst surface and adsorb the reaction gas until the reading of the nitrogen oxide analyzer remains stable, indicating that the adsorption equilibrium has been reached;

[0144] 3) After adsorption equilibrium, the temperature was programmed to rise from 100 °C to 550 °C at a heating rate of 5 °C / min;

[0145] At the same time, the reaction gas was passed through a drying tube and then introduced into a gas chromatograph and a nitrogen oxide detector to detect the conversion of methane and nitrogen oxides, and the NO under different temperature conditions was calculated using the following formulas (1) and (2): x Removal rate and CH4 conversion rate, and then record the relevant data;

[0146] Among them, the gas chromatograph in step 3) requires manual sampling (sampling once every 50°C), while the nitrogen oxide analyzer automatically samples (detects once every 5 minutes).

[0147] 3. Catalytic activity evaluation index and calculation formula

[0148] The catalyst activity is mainly due to nitrogen oxides NO x The removal rate, methane CH4 conversion rate and methane selectivity were comprehensively evaluated. x (de) represents the nitrogen oxide removal rate, as shown in formula (1), NO x The higher the (de) value, the better the catalytic activity; CH4(c) is used to represent the methane conversion rate, as shown in formula (2). CH4 is used as a reducing agent. The higher the conversion rate during the reaction, the more thorough the reaction is and the better the catalytic performance is.

[0149]

[0150]

[0151] In the formula, c(NO x_i ) indicates that NO x Initial concentration (ppm); c(NO x_o ) indicates that after the reaction, NO x Concentration (ppm); c(CH 4_i ) represents the initial concentration of CH4 before the reaction (ppm); c(CH 4_o ) represents the CH4 concentration (ppm) after the reaction.

[0152] Characterization and Performance Test Results

[0153] 1. MnO2, CoMn2O in Comparative Example 1 x 、ZnMn2O x 、NiMn2O x In the CH4-SCR denitrification catalytic activity test, the test results of CH4 conversion rate are as follows: Figure 1 shown.

[0154] Depend on Figure 1 It can be seen that within the temperature range of 200℃~450℃, the CH4 conversion rate of manganese-based composite oxides doped with different metals increases with the increase of temperature, among which NiMn2O x It starts to be activated at around 300°C, and the CH4 conversion rate reaches 7% at 400°C and 13% at 450°C; other metal-doped catalysts start to catalyze CH4 conversion above 350°C, and the CH4 conversion rate does not exceed 5% at 400°C, and the CH4 conversion rate of Co and Zn-doped catalysts is less than 10% at 450°C.

[0155] Although the nickel-doped manganese-based composite oxide (NiMn2O x ), the CH4 activation temperature is relatively low, but the maximum CH4 conversion rate can only reach about 13%.

[0156] This shows that the nickel-doped manganese-based composite oxide (NiMn2O x ) as a denitration catalyst, under the condition of denitration temperature of 150-450°C, there is NO x The problem of low removal rate and CH4 conversion rate.

[0157] 2. XRD (X-ray diffraction, abbreviated as: XRD) spectra of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2, as shown in FIG. Figure 2 shown.

[0158] Depend on Figure 2 It can be seen that: under the condition of Ni / Mn=1:2 (molar ratio), the H-Beta molecular sieve still maintains the H-Beta crystal structure after loading the nickel-manganese composite oxide. As the loading amount of the nickel-manganese composite oxide increases, the diffraction intensity of the characteristic peak of the H-Beta molecular sieve gradually weakens.

[0159] Regarding the XRD spectrum of the nickel-manganese composite oxide modified In / H-Beta catalyst in Example 2 (denoted as NiMn2@In / H-Beta-y, y represents the loading amount, y=0.5, 1, 1.5, unit: mmol Mn / H-Beta molecular sieve), no obvious characteristic peaks of nickel-manganese composite oxide were detected. This may be due to the thin coating layer of nickel-manganese composite oxide on the surface of H-Beta molecular sieve, and the characteristic peaks of nickel-manganese composite oxide are difficult to detect. At the same time, the coating of the nickel-manganese oxide layer reduces the diffraction intensity of the In / H-Beta molecular sieve, which also indirectly indicates that the nickel-manganese composite oxide and In / H-Beta are successfully composited.

[0160] 3. Scanning Electron Microscope (SEM) images of H-Beta molecular sieve, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2, as shown in FIG. Figure 3 As shown. Figure 3 In the figure, (a) and (e) are H-Beta molecular sieves, (b) and (f) are NiMn2@In / H-Beta-0.5, (c) and (g) are NiMn2@In / H-Beta-1, and (d) and (h) are NiMn2@In / H-Beta-1.5, which are SEM images at 2μm and 500nm scales, respectively.

[0161] Depend on Figure 3 It can be seen that the microscopic morphology of H-Beta molecular sieve is formed by the aggregation of particles, with a diameter of about 300nm to 400nm. For low-load NiMn2@In / H-Beta-0.5, only a small amount of nickel-manganese composite oxides attached to the surface of H-Beta molecular sieve were observed, and the size was small and the flaky characteristics were not obvious. This indicates that the concentration of reactants was low during the preparation process, which was not conducive to the nucleation and growth of nickel-manganese composite oxides. The nickel-manganese composite oxides were poorly formed on the surface of the molecular sieve and it was difficult to present a complete flaky or layered morphology (see Figure 3 (f)). For the medium-loaded NiMn2@In / H-Beta-1, it can be seen that a large number of flaky nickel-manganese composite oxides are formed on the surface of the molecular sieve, which have the "petal" characteristics of nickel-manganese composite oxides, and the "petals" are well formed and evenly dispersed on the surface of the molecular sieve. For the high-loaded NiMn2@In / H-Beta-1.5, it can be seen that the nickel-manganese composite oxides aggregate on the surface of the molecular sieve and are poorly dispersed.

[0162] 4. The specific surface area and pore size distribution data of the In / H-Beta catalyst in Comparative Example 3 and the catalysts with different nickel and manganese loadings in Example 2 are shown in Table 1.

[0163] Table 1 Specific surface area and pore size distribution data of catalysts with different nickel and manganese loadings

[0164]

[0165] It can be seen from Table 1 that the presence of a larger specific surface area and mesopores is conducive to providing more reaction sites and promoting material transport during the catalytic reaction. The specific surface areas of the In / H-Beta catalysts in Comparative Example 3 and the catalysts with different nickel-manganese loadings in Example 2 are both above 300 m 2 / g, and with the increase of the loading amount of nickel-manganese composite oxide, the specific surface area of ​​the catalyst decreased slightly, but the pore volume and pore size increased. The pore volume (0.394cm 3 / g) and pore size (6.2nm) are the largest, which is beneficial to the transport of substances during the catalytic reaction to a certain extent. Generally speaking, the larger the specific surface area, the better the catalyst is at reacting NO. x The stronger the adsorption capacity of CH4, the stronger the adsorption capacity of NO x For CH4 removal and activation, the size of the specific surface area does not play a decisive role in the catalyst activity, which can be combined with Figure 6 The conclusion was drawn based on the denitrification performance test results.

[0166] 5. The denitration catalytic activity test results of In / H-Beta catalyst, NiMn@In / H-Beta and NiMn2@In / H-Beta in Comparative Example 3 are shown in FIG. Figure 4 As shown; among them, Figure 4 (a) is NO x The removal rate test results, Figure 4 (b) is the test result of CH4 conversion rate.

[0167] Depend on Figure 4 It can be seen that: In / H-Beta catalyst, NO x The removal rate is almost zero, between 400℃ and 450℃, NO x The removal rate increased rapidly. At 550℃, NO x The removal rate reached a maximum of about 97%.

[0168] Compared with In / H-Beta catalyst, NiMn x The low-temperature activity of @In / H-Beta catalyst is significantly improved. At about 250℃, NO x The conversion begins to occur, and NO x The removal rate reached more than 99%. When the temperature was below 350℃, the NO x The removal rate is high, but the NO removal rate of NiMn2@In / H-Beta catalyst is x When the temperature is above 500℃, the removal rate of NO x At the same time, the catalysts with different nickel-manganese ratios in Example 1 can remove NO at around 480°C. x The removal rate reaches over 99%.

[0169] Regarding the CH4 conversion rate, in the CH4-SCR reaction process, the In / H-Beta catalyst begins to convert CH4 at around 350°C. When the temperature is 350°C to 550°C, the CH4 conversion rate gradually increases with the increase of temperature. When the temperature is 550°C, the CH4 conversion rate reaches 62.5%; NiMn x @In / H-Beta catalyst has started to activate at 300℃. As the temperature increases, the CH4 conversion rate reaches about 90% at 550℃, which shows that the CH4 conversion rate of In / H-Beta catalyst is significantly improved after being modified with a small amount of nickel-manganese composite oxide. Among the catalysts with different nickel-manganese ratios, NiMn2@In / H-Beta catalyst has the highest CH4 conversion rate, reaching 92% at 550℃. Compared with In / H-Beta catalyst, NiMn2@In / H-Beta prepared by combining nickel-manganese composite oxide and In / H-Beta x @In / H-Beta catalyst has significantly improved CH4-SCR denitrification performance in the absence of sulfur and water and below 550°C, which is conducive to widening the activity window towards low temperature. Among them, the performance of the catalyst with Ni / Mn=1:2 is better.

[0170] 6. The results of Fourier transform infrared spectroscopy (FTIR) of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2 are as follows: Fig.15 shown.

[0171] Depend on Fig.15 It can be seen that in the NiMn2@In / H-Beta catalysts with different loading amounts, as the loading amount of nickel-manganese composite oxide increases, the wave number is located at 1089cm -1 The infrared absorption peak at is the characteristic peak of Si-O-Al antisymmetric stretching vibration peak (related to the aluminum skeleton on the molecular sieve), and there is no obvious change, and the type and combing of the infrared absorption peak of the catalyst are basically unchanged, indicating that under the preparation conditions of Examples 1 to 3, the H-Beta molecular sieve remains stable and the skeleton does not change; the wave number is 791cm -1 The infrared absorption peak at can be attributed to the stretching vibration of Si-O-In, which indicates that in the process of indium ion exchange, indium ions replace hydrogen ions on Si-OH to form Si-O-In. The above analysis shows that the modification of nickel-manganese composite oxide has no effect on the framework structure of In / H-Beta molecular sieve.

[0172] 8. The CH4-SCR denitration test results of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2 are shown in Figure 6 ;in, Figure 6 (a) is NO x The removal rate test results, Figure 6 (b) is NO x Removal rate test results.

[0173] Depend on Figure 6 It can be seen that compared with the In / H-Beta catalyst, the NiMn2@In / H-Beta catalyst is improved by using the nickel-manganese complex to improve the H-Beta molecular sieve. x The performance is significantly improved, and the CH4 conversion rate is significantly improved at a relatively low temperature (550°C).

[0174] Specifically, regarding NO x In terms of removal rate, the removal rate of NO in NiMn2@In / H-Beta catalysts with different loading amounts was significantly higher at 250℃~550℃. x The overall trend of the removal rate basically increases with the increase of temperature. Among them, the removal rate of NO x The overall removal rate is excellent, followed by NiMn2@In / H-Beta-0.5 catalyst and NiMn2@In / H-Beta-1.5 catalyst. Further analysis shows that although the theoretical loading of NiMn2@In / H-Beta-1.5 catalyst is the highest and the NO x The removal rate is relatively high, but its overall denitrification catalytic activity is poor. After analysis, it can be inferred that this is due to the increase in the loading of nickel-manganese composite oxide, which causes the NiMn2@In / H-Beta-1.5 catalyst to produce obvious non-CH4-SCR side reactions in the low temperature zone (below 350°C), resulting in NO xThe removal rate is high, and after 400°C, the CH4-SCR reaction dominates. For NiMn2@In / H-Beta-1-500 and NiMn2@In / H-Beta-0.5-500 catalysts, the presence of nickel-manganese composite oxides promotes CH4 activation, thereby significantly increasing the denitrification activity of the catalyst. However, due to the large loading of nickel-manganese composite oxides on the NiMn2@In / H-Beta-1.5-500 catalyst, some active sites are covered, and due to its strong oxidizing property, CH4 undergoes a combustion reaction, so the denitrification activity is lower than that of In / H-Beta.

[0175] The CH4 conversion rate was further analyzed (see Figure 6 (b)), the CH4 conversion rate of NiMn2@In / H-Beta catalyst is significantly higher than that of In / H-Beta, which indicates that the composite of nickel-manganese composite oxide and In / H-Beta promotes CH4 activation, thereby improving the CH4 conversion rate. For NiMn2@In / H-Beta catalyst, as the loading of nickel-manganese composite oxide increases, the CH4 conversion rate increases, among which the CH4 conversion rates of NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 are slightly different. This shows that as the loading of nickel-manganese increases, the activation and oxidation of CH4 by the catalyst is enhanced. Combined with NO x Removal rate curve analysis shows that NiMn2@In / H-Beta-1 has the highest NO x The removal rate and high CH4 conversion rate indicate that NiMn2@In / H-Beta-1-500 exhibits the highest catalytic efficiency and good low-temperature activity in CH4-SCR. x However, this is mainly due to the increased oxidation caused by the increase in nickel and manganese loading, which promotes the removal of NO in the low temperature zone. x Low temperature conversion and catalytic oxidation of CH4.

[0176] The CH4 selectivity of the catalysts was analyzed. For NiMn2@In / H-Beta-0.5 and NiMn2@In / H-Beta-1 catalysts, the loading of nickel-manganese composite oxide promoted the activation of CH4 and improved the CH4 selectivity. Among them, the CH4 selectivity of NiMn2@In / H-Beta-1 catalyst was the highest, reaching 80% at 400°C. Above 500°C, the CH4 selectivity of NiMn2@In / H-Beta catalyst decreased, and the CH4 selectivity of NiMn2@In / H-Beta-1.5 catalyst was the lowest.

[0177] In summary, NiMn2@In / H-Beta-1 catalyst can achieve high NO x Removal rate, CH4 conversion rate and CH4 selectivity as well as good low-temperature activity, so it has relatively optimal CH4-SCR denitrification performance.

[0178] 9. In order to determine the chemical valence states of Ni, Mn, In and O on the surface of nickel-manganese composite oxide and analyze the effect of different loading amounts on the chemical valence states of the elements, X-ray photoelectron spectroscopy (XPS) was used to measure the Mn 2p 3 / 2 , Ni 2p, In 3d and O1s were analyzed. Mn2p of NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2 3 / 2 and Ni 2p 3 / 2 The X-ray photoelectron spectroscopy (XPS) spectra are as follows: Figure 7 and Figure 8 shown.

[0179] Depend on Figure 7 and Figure 8 It can be seen that: from Mn 2p 3 / 2 From the spectrum, it can be deconvoluted into two peaks with binding energy values ​​of 642.3eV and 643.5eV, respectively, which are attributed to Mn 3+ and Mn 4+ , Mn in NiMn2@In / H-Beta-1 catalyst 3+ The lowest ratio is Mn in NiMn2@In / H-Beta-0.5 and NiMn2@In / H-Beta-1.5. 3+ The ratios of the two are higher than the former, which indicates that the presence of Ni in the nickel-manganese solid solution (i.e., nickel-manganese composite oxide) inhibits the growth of Mn n+ ions, thereby inhibiting the diffusion of Mn 4+ To Mn 3+ At the same time, the loading amount of nickel-manganese composite oxide also affects the chemical state of the elements, which is caused by the different concentrations of reactants during catalyst preparation. For the NiMn2@In / H-Beta-0.5 catalyst, the nickel-manganese loading is low, which is not conducive to the formation of composite oxides, and the dissolution amount of Ni is low, so Mn 3+ When the nickel-manganese loading is high, part of the Ni may directly nucleate and crystallize in the form of nickel oxide, so the amount of Ni dissolved is also lower than the doping amount, thus 3+ The proportion increased.

[0180] In addition, the presence of In / H-Beta plays a certain role in limiting the nickel-manganese composite oxide loaded on its surface, further inhibiting the Mn 4+ To Mn 3+ However, in NiMn2@In / H-Beta-1.5, due to the high loading, the molecular sieve confinement effect is limited, and Mn 3+ / Mn 4+ The ratio has increased relative to NiMn2@In / H-Beta-1.

[0181] From Ni 2p 3 / 2 From the XPS spectra, the Ni 2p 3 / 2 The peak can be deconvoluted into three peaks: 850.1eV, 854.6eV and 861.1eV (satellite peak). The two binding energy peaks of 854.6eV and 861.1eV indicate that Ni exists mainly in a trivalent state; the 850.1eV peak corresponds to Ni 0 , Ni 0 The presence of Mn 2+ The generation of CH4 improves the redox properties of the catalyst and is beneficial to the activation of CH4.

[0182] The O1s XPS spectra of the In / H-Beta catalyst in Comparative Example 3, the In / H-Beta molecular sieve in Example 2, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 are as follows: Fig. 9 shown.

[0183] Depend on Fig. 9 It can be seen that the O 1s spectrum can be deconvoluted into two peaks at 529.8 eV and 531.4 eV, corresponding to the lattice oxygen (O latt ) and surface adsorbed oxygen (O ads ). This is mainly due to the adsorption and dissociation of gaseous oxygen or water on surface defects. According to the curve fitting analysis results, as the loading of nickel-manganese composite oxide increases, the O ads / O latt The O of In / H-Beta catalyst ads / O latt The Oads / Olatt of NiMn2@In / H-Beta-1 is 0.39, and that of NiMn2@In / H-Beta-1 is 0.48. This indicates that the proportion of surface adsorbed oxygen is increased after the nickel-manganese composite oxide is loaded, which plays an important role in the catalytic process. 3+ / Mn 4+ and O ads / O lattThe analysis of the ratios shows that the loading of nickel-manganese composite oxide can inhibit the 4+ To Mn 3+ The transformation of nickel-manganese composite oxide Mn 3+ / Mn 4+ The ratio is lower and contains more adsorbed oxygen (O ads ). Combined with the above ( Figure 6 ) analysis results show that this may be because the nickel-manganese composite oxide has a high adsorbed oxygen content, and after being loaded on In / H-Beta, the proportion of oxygen adsorbed on the catalyst surface increases. In addition, due to the interaction between the nickel-manganese composite oxide and In / H-Beta, the two produce a synergistic effect, further inhibiting the Mn 4+ To Mn 3+ This also promotes the increase of active oxygen content on the catalyst surface and improves the redox properties of the catalyst.

[0184] In 3d of the In / H-Beta catalyst in Comparative Example 3, the H-Beta molecular sieve in Example 2, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 5 / 2 XPS spectra, such as Fig.10 shown.

[0185] Depend on Fig.10 It can be seen from the above analysis that the catalytic activity of the nickel-manganese composite oxide modified In / H-Beta catalyst is better than that of the H-Beta catalyst, and In ions are introduced into the H-Beta molecular sieve framework through ion exchange. 5 / 2 From the XPS spectrum, the characteristic peak of In with a binding energy of about 445.4 eV to 445.9 eV in the nickel-manganese composite oxide modified In / H-Beta catalyst can be attributed to In2O3, while the peak with a binding energy of 446.1 eV to 446.7 eV is related to InO + This indicates that the indium in the nickel-manganese composite oxide modified In / H-Beta catalyst is InO + and In2O3. According to In 3d 5 / 2 Further analysis of the XPS spectrum shows that the loading of nickel-manganese composite oxide makes InO + The ratio of species increased, among which InO + The proportion of species is the highest, which may be due to the increase in the number of M-OH (M represents metal) on the catalyst surface due to the appropriate loading of nickel-manganese composite oxide. The increase in acid sites provides more sites for the exchange of indium ions, thus InO +The increase in species ratio is beneficial to improving the catalytic activity of the CH4-SCR reaction.

[0186] 10. The hydrogen temperature programmed reduction (H2-TPR) curves of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2 are as follows: Figure 5 The corresponding hydrogen consumption is shown in Table 2.

[0187] Table 2 H2 consumption of NiMn2@In / H-Beta catalysts with different nickel and manganese loadings

[0188]

[0189] Note: "NiMn2@In / H-Beta" in Table 2 means Ni:Mn=1:2 (molar ratio).

[0190] Depend on Figure 5 From Table 2, we can see that according to the H2-TPR curve, a reduction peak appears at about 310 °C for the In / H-Beta catalyst, which can be attributed to the InO + andIn + After loading the nickel-manganese composite oxide, the catalyst corresponds to InO + The reduction peak of NiMn2@In / H-Beta-1 shifts to low temperature and appears at around 300°C, and the peak area increases relative to In / H-Beta. In addition, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 also have two reduction peaks at around 350°C and 430°C, respectively. Combined with the H2-TPR analysis results of nickel-manganese composite oxides, it can be seen that these two reduction peaks correspond to Mn 4+ To Mn 3+ Transformation, and Ni 3+ and Ni 2+ This indicates that the modification of nickel-manganese composite oxide significantly improves the redox property of the catalyst, improves the low-temperature redox property of the catalyst, and enriches the redox sites on the catalyst surface. Combined with the analysis results in the previous article, it can be seen that this may be because the presence of nickel-manganese composite oxide greatly increases the amount of oxygen adsorbed on the catalyst surface, thus enhancing the redox property of the catalyst. In addition, InO +The change in the reduction peak also shows that the nickel-manganese composite oxide and In / H-Beta form a good chemical synergistic effect after the composite, rather than a simple mechanical mixing of the two. It can be seen from Table 2 that the H2 consumption increases with the increase in the loading amount of the nickel-manganese composite oxide. Among them, when the loading amount of the nickel-manganese composite oxide is 1.5mmol, the H2 consumption of the catalyst in the low temperature zone is the highest (2.219mmol / g), which is higher than the H2 consumption of the original In / H-Beta catalyst. Combined with the results of catalyst activity evaluation, under the same conditions, the NiMn2@In / H-Beta-1.5 catalyst has the highest NO at low temperature. x The removal rate and CH4 conversion rate all indicate that the loading of nickel-manganese composite oxide significantly increases the catalyst and improves the low-temperature redox performance of the catalyst. However, the CH4-SCR denitrification performance of the NiMn2@In / H-Beta-1.5 catalyst is not optimal, which indicates that the redox property of the catalyst and the denitrification activity are not completely proportional.

[0191] 11. The ammonia temperature-programmed desorption (NH3-TPD) curves of the In / H-Beta catalyst in Comparative Example 3, NiMn2@In / H-Beta-0.5, NiMn2@In / H-Beta-1 and NiMn2@In / H-Beta-1.5 in Example 2 are as follows: Fig.11 As shown, the NH3 desorption amount was analyzed and calculated based on the NH3-TPD curve.

[0192] Table 2 NH3 desorption amount of catalysts with different nickel and manganese loadings

[0193]

[0194] Note: The loading in Table 3 is the theoretical loading, which is based on Mn and calculated by the following formula:

[0195] Loading amount y = (n(KMnO4) + n(MnSO4)) / m(H-Beta molecular sieve),

[0196] In the formula, n(KMnO4) represents the amount of KMnO4, n(MnSO4) represents the amount of MnSO4, and m(H-Beta molecular sieve) represents the mass of H-Beta molecular sieve.

[0197] Depend on Fig.11 From Table 3, we can see that there are two desorption peaks on the NH3-TPD curve of In / H-Beta catalyst, which are located near 148℃ and 400℃ respectively. NH4 on the acid site +The NH3 desorption peak formed by decomposition at 400℃ is the desorption peak formed by the desorption of NH3 adsorbed on the Lewis acid site, which indicates that the surface contains Acid and Lewis acid, among which The acid sites are mainly weak acid centers, and the Lewis acid sites are strong acid centers. Two desorption peaks also appeared on the NiMn2@In / H-Beta catalyst. The peak position of the low-temperature desorption peak shifted toward the high-temperature direction compared with the In / H-Beta catalyst, and the peak area increased compared with In / H-Beta, indicating that the loading of nickel-manganese composite oxide not only increased the catalyst Acid strength, while also increasing the number of acid sites.

[0198] In each catalyst group The acid content of the catalyst was significantly higher than that of the Lewis acid. The B acid and L acid contents of the catalyst increased after loading the nickel-manganese composite oxide. This is because the presence of the nickel-manganese composite oxide increases the number of M-OH on the catalyst surface, thereby increasing the Acid sites, and the nickel-manganese composite oxide and In / H-Beta interact to form new oxygen-containing functional groups, thereby increasing the number of acid sites on the catalyst surface. In contrast, the NiMn2@In / H-Beta-1 catalyst has a larger number of acid sites, with an NH3 desorption amount of 4.553mmol / g, which is significantly increased relative to the In / H-Beta catalyst (NH3 desorption amount: 3.752mmol / g). Combined with the catalyst denitrification performance test, it can be explained that one of the reasons for the higher denitrification activity of the NiMn2@In / H-Beta-1 catalyst is that it contains more acid sites.

[0199] 12. The denitration catalytic activity test results of NiMn2@In / H-Beta-1-300, NiMn2@In / H-Beta-1-400 and NiMn2@In / H-Beta-1-500 in Example 3 are shown in FIG. Fig.13 As shown, Fig.13 (a) is NO x The removal rate test results, Fig.13 (b) is the test result of CH4 conversion rate.

[0200] Depend on Fig.13 It can be seen that in the CH4-SCR denitrification performance test results, the NO x Removal rate curves of NO removal of three groups of NiMn2@In / H-Beta-1 catalysts calcined at different temperatures xThe removal rate curves showed a similar trend, showing good low-temperature denitrification activity below 400°C. Overall, the catalysts obtained at different calcination temperatures showed that as the calcination temperature increased, NO x The removal rate first increased and then decreased, and the catalyst calcined at 400 °C had NO x Highest removal rate.

[0201] Moreover, from Fig.13 As can be seen in (a), the NiMn2@In / H-Beta-1-400 catalyst has more than 10% NO at 250°C. x Removal rate; NO at 400℃ x The removal rate is close to 50%, which is higher than that of In / H-Beta catalyst NO at the same temperature. x The removal rate is more than twice as high as that of NO x The removal rate of NO was 2.34%, while that of In / H-Beta catalyst was 1.32% at 500℃. x The removal rate reached 95%, which indicates that the activity window of the NiMn2@In / H-Beta-1-400 catalyst has obviously shifted toward the low temperature direction and has good low-temperature activity.

[0202] According to the CH4 conversion rate curve (see Figure 13(b)), the CH4 conversion rate of NiMn2@In / H-Beta-1 catalyst calcined at different temperatures is higher than that of In / H-Beta, among which the catalyst calcined at 400°C has the highest CH4 conversion rate. CH4 begins to convert at around 250°C, at which time the conversion rate is about 3%. As the temperature rises, the CH4 conversion rate rises slowly, reaching a CH4 conversion rate of about 23% at 400°C; after 400°C, the CH4 conversion rate rises rapidly, and at 450°C, the CH4 conversion rate of NiMn2@In / H-Beta-1-400 reaches 99%. This shows that the nickel-manganese composite oxide and In / H-Beta can work synergistically, increase the surface adsorption oxygen ratio of the catalyst, increase the redox property of the catalyst, promote CH4 activation, and thus improve the CH4 conversion rate.

[0203] The CH4 selectivity of NiMn2@In / H-Beta-1-400 is the highest. Below 400°C, the CH4 selectivity of NiMn2@In / H-Beta-1-400 is higher than 100%. As the temperature rises, the CH4 selectivity gradually decreases. At around 400°C, the CH4 selectivity is about 94%, and at 550°C, the CH4 selectivity drops to about 50%. This is because in the low temperature zone below 400°C, only a small amount of CH4 is activated and converted, while NO xThe conversion mainly occurs through non-CH4-SCR reaction pathways, so the CH4 selectivity exceeds 100%; when the temperature is higher than 400℃, part of the CH4 begins to undergo combustion reaction and is directly converted into CO2 and H2O, and does not participate in the CH4-SCR reaction. As the temperature rises, the proportion of CH4 undergoing combustion reaction gradually increases, so the CH4 selectivity decreases. At 550℃, NOx and CH4 are basically completely converted. At this time, about 50% of the CH4 participates in the CH4-SCR reaction to convert NO x The remaining 50% of CH4 undergoes combustion reaction and is directly converted into CO2 and H2O. Therefore, the CH4 selectivity drops to about 50% at 550°C.

[0204] 13. NiMn2O in Comparative Example 2 x -300, NiMn2O x -400 and NiMn2O x -500's XRD spectrum, such as Fig.12 The high resolution transmission electron microscope (HRTEM) image of NiMn2@In / H-Beta-1-400 in Example 3 is shown in FIG. Fig.14 As shown, in Fig.14 In the figure, (a), (b), (c) and (d) are HRTEM images of NiMn2@In / H-Beta-1-400 at different magnifications.

[0205] Depend on Fig.12 It can be seen from the XRD characterization results that when the calcination temperature is less than 400℃, NiMn2O x The catalyst is a single δ phase (corresponding to the standard card JCPDS 80-1098), where 2θ=12.2°, 24.7°, 36.5° and 65.7° correspond to the (001), (002), (-111) and (-312) crystal planes of δ-MnO2 respectively; when the calcination temperature is 500°C, the catalyst transforms into the α phase (corresponding to the PDF standard card 00-042-1348), and a small amount of NiMnO3 second phase is precipitated. This is because as the temperature rises, manganese dioxide transforms from the α phase to the δ phase, and the two-dimensional layered structure of MnO2 is transformed into a one-dimensional "tunnel" structure, the amount of Ni that can be dissolved is reduced, and part of Ni and Mn form the NiMnO3 second phase and precipitate. Since the nickel-manganese composite oxide on the surface of NiMn2@In / H-Beta catalyst is difficult to characterize directly by XRD, combined with the results of XPS and SEM, it can be inferred that the nickel-manganese composite oxide on the NiMn2@In / H-Beta catalyst includes MnO2 and NiMnO3.

[0206] Depend on Fig.14 It can be seen that: taking the NiMn2@In / H-Beta-400 catalyst as an example, the nickel-manganese composite oxide is coated on the surface of the H-Beta molecular sieve in a thin layer of "flower flakes", which basically maintains the basic morphology of the nickel-manganese composite oxide, indicating that nickel and manganese still exist in the form of composite oxides, but because only a very thin coating layer is formed on the surface of In / H-Beta, it is difficult to detect it by XRD. In addition, it can be seen from the HRTEM image that the loading of nickel-manganese composite oxide has no obvious effect on the pore structure of H-Beta, and the catalyst still maintains a rich pore structure. Fig.14 (c) clearly shows the lattice array of nickel-manganese composite oxide. The position marked in the figure is the (001) crystal plane of manganese-based oxide, and the interplanar spacing is about 0.72nm. The radius of nickel atoms is 1.62 angstroms, and the radius of manganese atoms is 1.79 angstroms. Nickel atoms are relatively small compared to manganese atoms. Therefore, when nickel atoms occupy the MnO2 lattice nodes, local lattice distortion will occur. This leads to differences in the reflection of electrons between nickel-doped sites and other sites, thus forming a contrast around nickel atoms. This can be used to distinguish the bright spots scattered between the lattices, which are doped nickel atoms. According to Fig.14 (d) From the HRTEM image, it can be clearly seen that Ni atoms are incorporated into the MnO2 lattice and occupy the lattice node positions, which further indicates that nickel and manganese still exist in the form of nickel-manganese composite oxides on the catalyst surface.

[0207] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A denitration catalyst, characterized in that: The denitration catalyst comprises indium, H-Beta molecular sieve and nickel-manganese composite oxide, wherein the indium and nickel-manganese composite oxide are both loaded on the surface of the H-Beta molecular sieve; the nickel-manganese composite oxide is in nano-layered form; The denitration catalyst is prepared by a preparation method comprising the following steps: 1) mixing permanganate, H-Beta molecular sieve and nickel salt, adding divalent manganese salt, performing hydrothermal reaction and first calcination to obtain nickel-manganese modified H-Beta molecular sieve; The first calcination is carried out under a protective gas atmosphere, and the temperature of the first calcination is 250° C. to 550° C.; 2) The nickel-manganese modified H-Beta molecular sieve and indium salt in step 1) are mixed, and ion exchange and a second calcination are performed to obtain a denitration catalyst; the second calcination is performed in an air atmosphere, and the temperature of the second calcination is 250° C. to 550° C.

2. The denitration catalyst according to claim 1, characterized in that: The ratio of the molar amount of the nickel-manganese composite oxide to the mass of the H-Beta molecular sieve is 0.05 mmol / g to 2 mmol / g.

3. The method for preparing the denitration catalyst according to claim 1 or 2, characterized in that: The following steps are involved: 1) After mixing permanganate, H-Beta molecular sieve and nickel salt, divalent manganese salt is added, and the mixture is subjected to hydrothermal reaction and first calcination to obtain nickel-manganese modified H-Beta molecular sieve; The first calcination is carried out under a protective gas atmosphere, and the temperature of the first calcination is 250° C. to 550° C.; 2) The nickel-manganese modified H-Beta molecular sieve and indium salt in step 1) are mixed, and ion exchange and a second calcination are performed to obtain a denitration catalyst; the second calcination is performed in an air atmosphere, and the temperature of the second calcination is 250° C. to 550° C.

4. The method for preparing the denitration catalyst according to claim 3, characterized in that: The ratio of the molar amount of manganese in step 1) to the molar amount of nickel in the nickel salt is 1:0.5 to 1:

5.

5. The method for preparing the denitration catalyst according to claim 3, characterized in that: In step 1), the molar ratio of the permanganate to the divalent manganese salt is 2:1 to 10:

1.

6. The method for preparing the denitration catalyst according to claim 3, characterized in that: The ratio of the molar amount of manganese in step 1) to the mass of the H-Beta molecular sieve is 0.1 mmol / g to 5 mmol / g.

7. A denitration device, characterized in that: Comprising the denitration catalyst according to claim 1 or 2.

8. Use of the denitration catalyst according to claim 1 or 2 in a selective catalytic reduction reaction.

Citation Information

Patent Citations

  • Efficient CH4-SCR denitration catalyst under oxygen-enriched condition and preparation method and application thereof

    CN106807440A

  • Modified manganese dioxide with high specific surface area, preparation method and application thereof

    CN113522227A